Motion of Enzyme‐Powered Microshell Motors. Issue 14 (27th May 2019) - Chen, Chengtao; He, Zhengqing; Wu, Jie; Zhang, Xueqing; Xia, Qianfeng; Ju, Huangxian
Abstract: Microshells are attractive in constructing bubble‐propelled micromotors due to the lower energy consumption for bubbles forming on a concave surface. In this work, enzyme‐powered microshell motors were fabricated on multimetallic (Au/Ag/Au) microshells along with the modification of catalase on its concave surface. The catalase triggered the decomposition of hydrogen peroxide to oxygen gas, hence propelling the autonomous motion of microshell motors. A size‐dependent motion behaviour was observed for the microshell motors in the form of slow tremble and fast translation motion for a size smaller and larger than 5 μm, respectively, according to the size, generation efficiency and ejection mechanism of bubbles and the intensity of Brownian motion. In addition, the effect of fuel concentration on the motion speed of microshells was dependent on whether the bubble generation was affected by the limited mass transfer in the microshell space. These findings play an important role for the design of microshell motors. Abstract : On the bubble : Enzyme‐powered microshell motors exhibit a bubble‐propelled motion with a size‐dependent behaviour in the form of slow tremble and fast translation motion for shells smaller and larger than 5 μm, respectively, due to the bubble size, generation efficiency and ejection way. The effect of fuel concentration on the motion speed of microshells was also size‐dependent because of the limited mass transfer in the microshell space.